Éros minoritaire : tel qu’il est vécu - Françoise d’Eaubonne (Genre, Sexualité et Société)
We offer here a chapter from Françoise d’Eaubonne’s book Eros minoritaire (Balland, 1970). Now impossible to find and unjustly forgotten, this book forms a particularly striking critique of a prevailing body of knowledge on sexuality. Disputing the scientific positions, which distinguish between inborn and acquired homosexuality, the author dismantels this mythology by showing its fallacious and repressive nature. Confronting a biologistic conception of human sexuality she denounces all forms of reductionist fundamentalisms and advocates for an acceptation of homosexuality “the way it's daily lived” by men and women.